Effect of citronella essential oil fumigation on sprout suppression and quality of potato tubers during storage. (30th June 2019) - Jia, Bin; Xu, Lixing; Guan, Wenqiang; Lin, Qiong; Brennan, Charles; Yan, Ruixiang; Zhao, Hui
Highlights: CEO fumigation suppressed sprouting during potato storage. CEO fumigation regulated GA3 in potato tubers. CEO fumigation diminished the level of α-solanine in potato skin and flesh. Dual-phase fumigation is more effective for potato sprouting suppression. Abstract: Effect of citronella essential oil (CEO) fumigation on sprout suppression and quality of potato tubers during storage was investigated. Potato tubers were treated under conditions of single-phase (30 μL L −1, 0–10 d) and dual-phase (30 μL L −1, 0–10 d; 30 μL L −1, 35–90 d) fumigation. Changes in germination rate, weight loss, starch, reducing sugar, gibberellins (GA3 ), and α-solanine were measured. The results showed that CEO fumigation could control sprouting and improve the quality of potato tubers during storage compared to the non-treated tubers. CEO treatments inhibited the degradation of starch and the increase of reducing sugar content. The production of gibberellins (GA3 ) was suppressed, and the levels of α-solanine in the skin and flesh of potato tubers were decreased by CEO fumigation. Dual-phase CEO fumigation had a better effect on sprout suppression than single-phase fumigation, and possesses potential for postharvest application.